Perspectives of people with inherited retinal diseases on ocular gene therapy in Australia: protocol for a national survey. Issue 6 (22nd June 2021) - Mack, Heather G; Chen, Fred K; Grigg, John; Jamieson, Robyn; De Roach, John; O'Hare, Fleur; Britten-Jones, Alexis Ceecee; McGuinness, Myra; Tindill, Nicole; Ayton, Lauren
Abstract : Introduction: Voretigene neparvovec-rzyl (Luxturna) was approved by the Australian Therapeutic Goods Administration on 4 August 2020 for the treatment of biallelic mutations in the RPE65 gene, a rare cause of congenital and adult-onset retinal dystrophy (predominantly Leber congenital amaurosis). Previous studies have shown that individuals who might participate in gene therapy trials overestimate clinical effect and underestimate risks. However, little is known about the perspectives of patients who may be offered approved gene therapy treatment for ocular conditions (as distinct from participating in clinical trials of gene therapy). The main objective of this study is to develop a tool to assess knowledge, attitudes and perceptions of approved and future genetic therapies among potential recipients of ocular gene therapy. In addition, we aim to assess the quality of life, attitudes towards clinical trials and vision-related quality of life among this cohort. Methods and analysis: A new 'Attitudes to Gene Therapy for the Eye' tool will be developed following consultation with people with inherited retinal disease (IRD) and content matter experts. Australians with IRD or their guardians will be asked to complete an internet-based survey comprising existing quality of life and visual function instruments and items for the newly proposed tool. We expect to recruit 500 survey participants from patient support groups, the practices of Australian ophthalmologists who are specialists in IRD and Australian ophthalmic research institutions. Launch is anticipated early 2021. Responses will be analysed using item response theory methodology. Ethics and dissemination: This study has received ethics approval from the University of Melbourne (#2057534). The results of the study will be published in a peer-reviewed journal and will be presented at relevant conferences. Organisations involved in recruitment, and the Patient Engagement Advisory committee will assist the research team with dissemination of the study outcomes.